The usage by the modern school an experience of high school pupils' healthy life style forming (the second part of XX century). - Iermakova T.S (Kharkov National Pedagogical University, 2010)
Directions of perfection of the system of a teaching and educational process with schoolchildren are considered. It is marked that an account of experience of schoolchildren's healthy life style forming is a necessity and pedagogical expedient. It is marked the necessity of perfection of maintenance of the modern schoolchildren's healthy life style forming for educational time and their free time. It is set that approaches to forming theoretical knowledge and studies practical skills need changes in accordance with a new health saving environment. It is well-proven that modern school needs address to experience past.